The Bridge - A Bridge Back into Community - Diarbakarli, Jalal (My University, 2021)
Mental illnesses are steadily increasing among people worldwide, especially in countries with high GDP rates. Its effects are reflected on individuals, families, and whole societies. In Sweden, mental illnesses are in third place among diseases leading to death. However, an addressed gab can be seen in its healthcare system. In their long journey to complete recovery, patients with mental illnesses usually visit more than one healthcare service provider; primary care centres, department of social services, residential and daycare centres, clubhouses, or psychiatric hospitals, to receive the holistic care they need. Despite the vital role that psychiatric rehabilitation plays in the patient’s treatment and recovery journey, it has unfortunately not been perceived as a phase that requires dedicated facilities that offer a holistic approach to psychiatric rehabilitation in Sweden. The purpose of this research is to emphasize the strong impact of architecture and landscape elements on promoting psychological health and wellbeing when sustainable- and health-promotive approaches, including Salutogenesis and biophilia, are employed in the design. The research designs a health-promoting centre that offers a holistic psychiatric rehabilitation approach to bridge patients, in their aftercare phase of treatment, back to their communities and have a healthy and functional life. The impact of the centre’s varied activities and services are extending to include and engage with a broad group of society. A research-for-design approach has been applied in the study. Literature reviews, reference projects, interviews, and implications of evidence-based design findings, and health- promotive approaches, will be employed in the design process. The outcome leads to the fact that architecture, together with nature and other health-promotive approaches if applied wisely, could work as a catalyst in promoting societal health and wellbeing. Furthermore, it could play a key role in fighting the stigma associated with mental-health-related facilities.
Keywords: Healthcare, psychiatric rehabilitation, health-promotion; salutogenesis, biophilia, evidence based design, design for research